Керамічний посуд пізньосередньовічної Вінниці (за матеріалами археологічних досліджень 2013 р.) - Виногродська, Л.І.; Калашник, Є.С. (Археологія, 2015)
У публікації аналізується комплекс керамічного посуду, що виявлений під час археологічних розкопок на території домініканського монастиря XVII—XVIII ст. у м. Вінниця в 2013 р. Установлено асортимент виробів, виділено основні морфологічні та стилістичні ознаки подільського посуду з Вінниці, простежено подібність керамічних форм археологічним знахідкам з інших регіонів України. Analyzed in the article is a collection of ceramic pottery dated form the 16th to the 18th centuries found during the excavations on the territory of the Dominican monastery in Vinnytsia in 2013.
The materials analysed represent two chronological periods in everyday life development in the Late Mediaeval Vinnytsia. The first stage, the 16th century, is defined by a small range of ware with mostly smoked jugs predominating, and this feature is on a whole common for Ukrainian left bank region in this period. The second stage, the 17th ad the 18th centuries, is distinguished by a sudden extension of wares’ range, by the production quality, and by the richness of ornamentation. These features are related by the authors with everyday life of Jesuit order monks whose culture represents examples common in Western European castles. The Jesuit monastery was situated directly near the Dominican monastery since the beginning of the 17th century. Broken pottery with other scrap fell into the cultural layer of adjusted territories.
The circle of analogies to the findings allows tracing that most of ceramic forms of the 17th and the 18th centuries are identical with findings from other regions of Ukraine: Volyn, Sloboda region, the Dnipro River middle region, Poltava region, and Chernihiv-Siveria. This fact evidences for the unification of everyday life and cultural unity on both sides of the Dnipro River. В статье анализируется коллекция керамической посуды ХVІ—ХVІІІ вв., найденной во время раскопок на территории Доминиканского монастыря в Виннице в 2013 г.
Проанализированный материал представляет два хронологических периода в развитии быта позднесредневековой Винницы. Первый этап — ХVІ в. — характеризуется небольшим ассортиментом посуды, в котором доминируют прежде всего дымленые горшки, что в целом характерно для Правобережной Украины в этот период. Второй этап — ХVІІ—ХVІІІ вв. — отличается резким увеличением ассортимента посуды, качеством производства и богатством орнаментации. Эти характеристики связываются автором с бытом монахов иезуитского ордена, культура которых презентует образцы распространения в замках Западной Европы. Иезуитский монастырь с начала ХVІІ в. располагался в непосредственной близости к доминиканскому. Разбитая керамическая посуда, в числе других отходов попадала в культурный слой прилегающих территорий. Круг аналогий находкам позволяет проследить тождественность большинства керамических форм ХVІІ—ХVІІІ вв. археологическим находкам из других регионов Украины — Волыни, Слобожанщины, Среднего Поднепровья, Полтавщины, Чегнигово-Сиверщины. Это свидетельствует об унификации быта и культурное единство территорий обоих берегов Днепра.